A coupled heat transfer and tritium mass transport model for a double-wall heat exchanger design for FHRs. (December 2018) - Zhang, Sheng; Wu, Xiao; Shi, Shanbin; Sun, Xiaodong; Christensen, Richard; Yoder, Graydon
Highlights: Tritium control is potentially a critical issue in FHRs and MSRs. A double-wall heat exchanger design is a promising option for FHR tritium control. A coupled heat and mass transfer model is developed for the DWHX design. The NSGA was applied to optimize the NDHX design for AHTR's DRACS. Abstract: Tritium production rate in Fluoride salt-cooled High-temperature Reactors (FHRs) was estimated to be several orders of magnitude higher than that in Light Water Reactors (LWRs). Due to the high permeability of tritium at elevated temperatures, a double-wall heat exchanger design consisting of inner and outer tubes was proposed to significantly reduce the tritium permeation through the heat transfer surfaces to, ultimately, the environment. A coupled heat transfer and tritium mass transport model was developed for performance analysis of a double-wall Natural Draft Heat Exchanger (NDHX) design. Since there was no published experimental data available in the literature involving both heat transfer and mass transport simultaneously, these two sub-models, i.e., heat transfer sub-model and mass transport sub-model, were benchmarked against available experimental data separately. For the heat transfer sub-model, the discrepancies for the predicted temperatures and heat transfer coefficients compared with their individual experimental data are within 16% and 24%, respectively. For the mass transport sub-model, the relative discrepancies between the model predictions and the experimental data are 23–44% at temperatures from 700 to 1000 °C (23–35% at the salt temperatures from 700 to 800 °C, between which the maximum salt temperature is expected in FHRs). This coupled heat transfer and mass transport model was then used to analyze a double-wall NDHX design for the Advanced High-Temperature Reactor (AHTR), a pre-conceptual FHR design developed by the Oak Ridge National Laboratory, from the following four tube configurations: 1) inner plain tube with outer plain tube (IPOP); 2) inner plain tube with outer fluted tube (IPOF); 3) inner fluted tube with outer plain tube (IFOP); and 4) inner fluted tube with outer fluted tube (IFOF). The results show that for the heat transfer performance, the IFOF design is slightly superior to the IPOF design and that both are significantly superior to the IFOP and IPOP designs. For the mass transport performance, the IFOP design is slightly superior to the IFOF design, and both significantly over perform the IPOP and IPOF designs. In addition, Non-dominated Sorting in Generic Algorithms (NSGA) was applied for the design optimization of a potential NDHX with the IFOF configuration for AHTR.